Recuperação da magnésia a partir de solução de sulfato de magnésio por precipitação e calcinação da nesqueonita - Cássia Ribeiro Souza (2020)
The magnesium carbonate as nesquehonite (MgCO3.3H2O) has shown to be increasingly attractive as a source of magnesium oxide (MgO), as it is a precipitate of easy filtration and which, after calcination, can produce a high- quality product. In addition to having high potential as CO2 sequestrating, the nesquehonite can also be used in the storage of nuclear waste and in the manufacture of functional and environmental protection materials. As part of nickel’s processing, magnesia (MgO) is used as a precipitating agent for MHP (Mixed Hydroxide Precipitation) in an intermediate stream of ore leaching by sulfuric acid, rich in nickel and cobalt, generating a concentrated stream in magnesium sulfate. In this context, the present work aims to obtain a reactive magnesia from a synthetic solution of magnesium sulfate that simulates the conditions of the effluent of the nickel processing industry by nesquehonite precipitation followed calcination. For this, the system was modeling using the software PHREEQC with initial magnesium concentration in a solution equal to 43 g.L-1 at 25ºC and it was possible to predict an Mg consumption equal to 99.1%, without additional pH control. Experimentally, this consumption was 95.4%, which corresponds to a simulation efficiency of 96.1%. The pH variation during the test showed the expected behavior when adding Na2CO3 as a precipitating agent. It was possible to observe a profile for the extent of precipitation by calculating the supersaturation index of the system and the correlation with the conductivity values obtained by its continuous monitoring. In order to obtain the final product, the precipitated solid obtained was subjected to calcination. First, it was made a design of experiments for temperature (450 to 650°C) and time (2 to 6 hours). It was observed after the adjustment of the model that the best conditions were obtained for high calcination temperatures and short time operation, or vice versa. Subsequently, the solid was again calcined and the temperatures of 450 and 550ºC for 60 minutes showed activity of product equal to 14.7±0.6 and 16.2±0.3 seconds, respectively, similar to the commercial magnesia activity value (14.63±0.04 seconds). The solids obtained in this work presented largely nesquehonite (precipitation) and periclase (calcining), although it was observed the presence of sodium sulfate in the solid. The study suggests the possibility of using PHREEQC in the modeling of liquor magnesium carbonate for nickel’s processing with nesquehonite formation, which after calcination at a variable temperature of 450-550ºC can produce a high quality magnificent similar to the commercial product and the circularity increases in nickel’s processing.